2015
DOI: 10.1155/2015/329831
|View full text |Cite
|
Sign up to set email alerts
|

Rhein ElicitsIn VitroCytotoxicity in Primary Human Liver HL-7702 Cells by Inducing Apoptosis through Mitochondria-Mediated Pathway

Abstract: Objective. To study rhein-induced apoptosis signaling pathway and to investigate its molecular mechanisms in primary human hepatic cells. Results. Cell viability of HL-7702 cells treated with rhein showed significant decrease in dose-dependent manner. Following rhein treatment (25 μM, 50 μM, and 100 μM) for 12 h, the detection of apoptotic cells was significantly analyzed by flow cytometry and nuclear morphological changes by Hoechst 33258, respectively. Fatty degeneration studies showed upregulation level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 82 publications
(96 reference statements)
0
19
0
Order By: Relevance
“…Rhein, a component of traditional Chinese medicines such as P. multiflorum and R. palmatum L., may be one of the causes of liver damage caused by these Chinese medicines. It has been demonstrated to induce apoptosis activities in many cell lines, and caused hepatotoxicity in primary rat hepatocytes …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhein, a component of traditional Chinese medicines such as P. multiflorum and R. palmatum L., may be one of the causes of liver damage caused by these Chinese medicines. It has been demonstrated to induce apoptosis activities in many cell lines, and caused hepatotoxicity in primary rat hepatocytes …”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated to induce apoptosis activities in many cell lines, and caused hepatotoxicity in primary rat hepatocytes. [33][34][35] In this study, we conducted a series of experimental procedures of rhein and assessed rhein cytotoxicity on L02 cells. It has been suggested that more than one assay should be used to determine the cytotoxicity of chemicals for the reliability of the data.…”
Section: Discussionmentioning
confidence: 99%
“…When apoptosis occurs, phosphatidylserine (PS) located in the inner cytomembrane moved to the external cytomembrane, which could be specially combined by Annexin V, thus early apoptosis could be discovered by testing PS using flow cytometry (26). With apoptosis further proceeding, and through staining, condensed chromatin, nuclear fragmentation and apoptotic bodies in apoptotic cells exhibited intense fluorescence under a fluorescence microscope (27).…”
Section: Discussionmentioning
confidence: 99%
“…Data are given as the relative ratio of green to red fluorescence intensity, showing the level of depolarization of the mitochondrial membrane potential (Bounda, Zhou, Wang, & Feng, 2015). Harvested cells were treated with JC-1 (10 μg/mL) (Beyotime Institute of Biotechnology, Shanghai, China) at room temperature for 5 min to detect mitochondrial membrane potential (ΔΨm) depolarization.…”
Section: Determination Of δψMmentioning
confidence: 99%
“…States of ΔΨm depolarization were determined by flow cytometry and CytExpert software (version 1.2; Beckman Coulter, Inc., Brea, CA) was used to analyze the data. Data are given as the relative ratio of green to red fluorescence intensity, showing the level of depolarization of the mitochondrial membrane potential (Bounda, Zhou, Wang, & Feng, 2015).…”
Section: Determination Of δψMmentioning
confidence: 99%